ENIUS. European Network of multidisciplinary research to Improve the Urinary Stents. COSTS Actions. CA16217. European Cooperation in Science & Technology - Ambardjieva, Martina; Sofronievska-Glavinov, Maja (Springer Science and Business Media LLC, 2020)
The purpose of this study is to determine the effects of intubation, the impact of complications and to estimate the necessity of improving urinary stents used during pregnancy. Hydronephrosis during pregnancy most commonly develops as a result of compression of the ureters as well as the effect of progesterone on the smooth muscle relaxation. Clinical significance of hydronephrosis lies in the association between ureteral obstruction and the high frequency of ascending urinary tract infection during pregnancy. Most of the cases of symptomatic hydronephrosis in pregnancy resolve with conservative measures with a rare need of stent insertion. When needed, ureteric stents are inserted with local anaesthesia under transabdominal US guidance. Pain and discomfort are common experiences during the procedure. The most common complication of ureteric stents is encrustation which occurs in this population likely secondary to the changes in urinary chemistry during pregnancy, such as hypercalciuria and hyperuricosuria. Ureteric stents placed in pregnant women are generally exchanged every 4–6 weeks in order to avoid encrustation and potential obstruction, necessitating the repeated cost and morbidity of repeated procedures. Infection and migration are other complications of internal stent replacement. In addition, this repetitive procedure can induce rupture of the intrauterine membranes in some cases, or can induce preterm delivery due to invasive and uncomfortable procedure especially in the third trimester of pregnancy. Sometimes for removal of the ureteric stent performing ESWL is inevitable because severe incrustation prevents stent removal after delivery, especially for patients without periodical replacement of the stents. Multiple procedures, morbidities, antibiotics, dietary calcium restriction and pain associated with ureteral stents replacement can all have a negative impact on a pregnancy. For these reasons, biodegradable stents should be preferred and are ideal solution in the properly selected pregnant patient, particularly as this device technology continues to improve.
Necessity of improving urinary stents used during pregnancy